Step-by-step explanation:
So in the equation given, y = 2x - 3
you substitute x for whats given in the table in the x column.
Example
In the graph the first number under the x colum is -1.
y = 2x - 3 in the equation you take out x and put -1.
So now the equation becomes y = 2 × -1 - 3.
Using bedmas to solve the question you should get -5
Which now means y = -5
To plot the point now x would be -1 and y would be -5 (-1, -5)
Same thing for the second number in the x Column.
y = 2 × 1 - 3 which equals -1
To plot it
x = 1 y = -1. (1, -1)
And for the last number 3.
Agai. You substitute x for 3 which makes the equation y = 2 × 3 - 3
this gives you 3 and to plot it
x would be 3 and y would be 3
Answer:
10 with a remainder of 1
Step-by-step explanation:
and also, you should use a program like cymath for that. Only use brainly for problems that cant be answered by a website like that.
Good luck!
X + y = 1
x + 3y = 9
Subtract the second equation from the first.
-2y = -8
divide both sides by -2
y = 4
Plug 4 back into either equation and solve for x.
x + y = 1
x + 4 = 1
subtract 4 from each side
x = -3
(-3, 4)
Answer:
1. 144 2. 16 3. 1 4. 3x-6
Step-by-step explanation:
So think of this as a function in a function. So you work from the inside to the outside. So for problem 1, we start with f(4)) [you read it "f of 4"] so what is the solution when x = 4, since f(x) means the function of x so f(4) means 'the function of 4' inside f(x).
Since f(x) = 3x then f(4) = 3(4) [notice how you substitute the 4 everywhere you see a letter x]
so f(4) = 12, now you work the next part h(f(4)) since f(4)=12 then h(12)
So take the h(x) function which is h(x) =
then h(12) =
so h(12) = 144